2016
DOI: 10.1016/j.ijmyco.2016.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Alternate efflux pump mechanism may contribute to drug resistance in extensively drug-resistant isolates of Mycobacterium tuberculosis

Abstract: Our data show an nsSNP in the drrA efflux pump gene that may result in upregulation of drug efflux mechanisms in MTB strains. It is therefore imperative to understand the mechanism of efflux and its role in drug resistance, which will enable the identification of new drug targets and development of new drug regimens to counteract the drug efflux mechanism of MTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hence, detection of the mutation of gyrA gene could be used to predict OFX resistance in Chongqing. Notably, there were 13 OFX-resistant strains without mutation located in gyrA , indicating that there are other mechanisms related to OFX resistance, such as cell wall permeability and drug efflux pump [ 30 , 31 ]. On the other hand, there were 5 OFX-susceptible strains with mutation of gyrA gene, including one strain with an Gly88Ala mutation, two strains with Ala90Val mutation, and two strains with Asp94Ala mutation, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, detection of the mutation of gyrA gene could be used to predict OFX resistance in Chongqing. Notably, there were 13 OFX-resistant strains without mutation located in gyrA , indicating that there are other mechanisms related to OFX resistance, such as cell wall permeability and drug efflux pump [ 30 , 31 ]. On the other hand, there were 5 OFX-susceptible strains with mutation of gyrA gene, including one strain with an Gly88Ala mutation, two strains with Ala90Val mutation, and two strains with Asp94Ala mutation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This might limit the detection of the variety of gene mutations. Third, there was still some drug-resistant isolates that could not be explained in our study, such as mutations at other gene regions [ 35 ], permeability of cell membrane, and overexpression of drug efflux pump gene [ 30 , 31 ]. Therefore the other mechanisms of OFX resistance or KAN resistance will be detected in the further study and whole-genome sequencing might be needed to find more loci associated with drug resistance and to improve the performance of the sequencing-based assay.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed drug resistance is usually caused by mutations, the inhA structural gene or the inha promoter region 57 , i.e ., resistance to INH caused by mutation of katG gene. Other studies showed that alternate efflux pump, which pumping drug out of cell, could be another cause of drug-resistance 8, 9 . However, these mechanisms could explain only part of all the M.tb drug-resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still a few other mutations that can lead to resistance ( e.g. those that cause greater expression and/or activity of efflux pumps which remove the drug from within the tubercle bacillus) [ 17 ]. Over the next few years, mapping of DST with genetic mutations identified by whole-genome sequencing (WGS) will begin to define how the phenotypic and genotypic resistance relate to each other.…”
Section: Molecular Drug-resistance Testingmentioning
confidence: 99%